2020
DOI: 10.18203/2349-3291.ijcp20200110
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of short stature in children attending pediatric endocrinology clinic of a tertiary care hospital in Bangladesh

Abstract: Background: Short stature is a common problem to practicing pediatricians. It results from various etiologies, which are categorized as normal variants and pathological causes. Normal variant short stature consists of Familial Short Stature (FSS) and Constitutional Growth Delay (CGD), while pathological causes are subdivided into endocrine diseases, clinically defined syndromes, chronic diseases, metabolic diseases and others. There are not so much data available in Bangladesh in this respect. So, present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Current study showed that normal variant short stature (NVSS) was equal to pathological short stature (48% vs 52%) which is found consistent with the findings of other studies 10,15 , but it differs from one study from Bangladesh. 16 In this study FSS was more common in females than males (21% vs 15%) whereas in case of CDGP males outnumbered females (8% vs 6%). This finding is similar with other studies.…”
Section: Discussionmentioning
confidence: 41%
“…Current study showed that normal variant short stature (NVSS) was equal to pathological short stature (48% vs 52%) which is found consistent with the findings of other studies 10,15 , but it differs from one study from Bangladesh. 16 In this study FSS was more common in females than males (21% vs 15%) whereas in case of CDGP males outnumbered females (8% vs 6%). This finding is similar with other studies.…”
Section: Discussionmentioning
confidence: 41%
“…Therefore3, SS is defined as body height below the 3rd percentile on a percentile grid, or below 2 standard deviations (-2SD) from the mean for a particular population. The problem involves roughly 3% of children [10].…”
Section: Short Stature (Ss) -Disorders Of Height and Developmentmentioning
confidence: 99%